Pro SQL server 2008 XML - Coles, Michael (Expert's voice in SQL server., 2008)
Knowledge and ability to apply XML are de rigueur in today's world, and SQL Server developers and administrators are no exception to that rule. Pro SQL Server 2008 XML is your key to unlocking the powerful XML feature set first introduced in SQL Server 2005 and since refined in SQL Server 2008. Author Michael Coles shows how to store XML using SQL Server's built-in XML data type. Learn to query and manipulate XML data using standard technologies such as XQuery and XSLT. No SQL Server database professional can afford to be without knowledge of the XML feature set. Pro SQL Server 2008 XML delivers on the knowledge that you need to remain competitive in your career. Shows how to store, query, and manipulate XML documents in SQL Server Provides step-by-step examples showing best practices and advanced features Accurately discusses how SQL Server's XML feature set stacks up against the ISO XML standards.